Kings Road
In the above diagram the track coloured blue represents an intended alteration in the Kings Road leading from Mount Charles, Giddy Hall to Black River. It commences at the Kings Road near Mount Pleasant settlement and passing through Brown Hall settlement and Luana Pen intersects the Kings Road in Luana land the distance being 77 chains. 1823.
Keywords: St. Elizabeth -- Maps; Maps; Mount Charles; Giddy Hall; Mount Pleasant Settlement; Brown Hall Settlement